Cold atmospheric plasma effectively kills chordoma cells through induction of intracellular reactive oxygen species - Sophie Peeters; Peter B. Wu; Blake Haist; Amber Armellini; Wi Jin Kim; Zhitong Chen; Richard Obenchain; George Ayad; Weihong Ge; Aparna Bhaduri; Graeme Sabiston; Robert M. Prins; et al. (Scientific Reports)
Abstract Chordomas remain one of the most difficult-to-treat of skull base tumors. The best chance of survival and cure to date is with en bloc radical surgical resection, followed by adjuvant radiotherapy. Oftentimes, tumor infiltration into functionally critical, or difficult-to-access areas, precludes optimal resection. The median overall survival for these tumors is 116 months. Cold atmospheric plasma (CAP) is generated by applying a high voltage electric field to helium or argon feed gases, resulting in reactive atmospheric species. Over the past decade, CAP has been applied experimentally in a number of oncologic conditions and has demonstrated anti-tumor effects both in vitro and in vivo. Additionally, CAP has been shown to increase cancer cells’ sensitivity to radiation and could therefore be a useful tool in improving chordoma recurrence rates as an intraoperative adjuvant therapy to the current standard of care. To date, there are no studies in the literature examining the efficacy of CAP in inducing cytotoxicity in chordoma. We treated CH2, CH7 and UM-Chor1 chordoma cells with CAP, measuring resulting cell viability and intracellular ROS accumulation. Here, we show a dose-dependent increase in intracellular ROS and cell death with direct CAP exposure in vitro, finding an exquisite sensitivity of chordoma cells to CAP-mediated cytotoxicity.